Evaluation of cyclosporine a as a cardio- and neuroprotective agent after cardiopulmonary resuscitation in a rat model - Knapp, Jürgen; Roewer, Joachim; Bruckner, Thomas; Böttiger, Bernd W.; Popp, Erik (Shock, 2015)
The immunosuppressant drug cyclosporine A (CsA) is a direct inhibitor of the mitochondrial permeability transition pore, which is the common end point of many pathways of ischemic preconditioning and postconditioning. We studied the neuroprotective and cardioprotective effect of CsA after cardiac arrest (CA) in a rat model of cardiopulmonary resuscitation.